Pengaruh Profitabilitas, Leverage, Dan Ukuran Perusahaan Terhadap Pengungkapan Corporate Social Responsibility (CSR) - Febrianti, Feni; Kaharti, Eni (Politeknik Sawunggalih Aji, 2024)
This study aims to determine the effect of profitability, leverage, and firm size on the disclosure of corporate social responsibility (CSR) in food and beverages sub-sector companies listed on the IDX. Profitability is measured using ROA, leverage is measured by DER, company size is measured by SIZE, and CSR is measured by global reporting invinitive (GRI-G4) 91 points. The method used in this study is a quantitative method. The population in this study is the food and beverages sub-sector companies listed on the IDX. The sample in this study was taken using purposive sampling method. The data sources in this study were obtained from the official website of the Indonesia Stock Exchange (IDX) or the website www.idx.co.id using documentation techniques. Data analysis in this study used multiple regression analysis. Based on the results of data analysis, it can be seen that profitability has no effect on CSR disclosure, leverage has a neat effect on CSR disclosure and company size has no effect on CSR disclosure in food and beverages sub-sector companies listed on IDX in 2018-2020. All independent variables together have a significant effect on CSR disclosure. Keywords: Disclosure of corporate social responsibility, profitability, leverage, company size